Genetic control of traits determining phosphorus uptake by rice varieties (Oryza sativa L.) - J. K. Goncharova; E. M. Kharitonov (Вавиловский журнал генетики и селекции)
The objectives of this research are: (1) to find genetic material associated with high growth rate and maximum size of root system, (2) to study polymorphism of rice varieties for markers connected with genes defining effective utilization of phosphorus, (3) to estimate the possibility of using listed SSR markers for introgression of previously mapped genes, and (4) to classify donor accessions found in the Russian gene pool into groups according to the probability of stability formation by various genetic mechanisms. Traits determining the rate of phosphorus uptake by rice varieties and their inheritance are discussed. Polymorphism of 72 rice accessions of Russian and foreign breeding by the rate of the formation of the root system and its size at maturity is considered. The highest rates of root system formation are found in varieties Liman, Arborio, Dalnevostochnyi, Selenio, Oceano, Atlant, Musa, Fontan, Cerere, Sharm, Serpentine, Khankaiskii 52, Leader, Boyarin, and Druzhnyi. Russian varieties outperform Italian ones in growth rate. Root weights at the maturation stage varied from 1,5 to 4,5 grams. Varieties Carnise, Rapan, Onix and G-57 display the greatest root weights at the maturation stage. Root lengths at the maturation stage varied from 17 to 26 cm. Varieties D 25-2, G 75-5, Ryzhik, G-52, Krepysh, and Snezhinka had the maximum values. Study of polymorphism of Russian and foreign varieties on the markers associated with the genes determining uptake of phosphorus has revealed polymorphism for all markers; thus, marker-assisted selection can be applied to them in breeding for this trait. The maximum number of alleles is noted for the RM 247 marker, located on chromosome 12.